Single droplet microrheology - Harrold, Victoria C. (2021)
The vibration of microlitre sized drops in partial contact with a substrate was used to extract the rheological properties of multicomponent fluids. Sessile and pendant drop vibration was triggered using a short mechanical impulse. Sessile drops were supported on superhydrophobic surfaces and their vibration monitored using laser light, refracted through the drops and focussed on the sensor of a photodiode. Pendant drops were suspended from clean pipette tips and their vibration was recorded using a high speed camera. Time dependent photodiode intensity/centre of mass variations were Fourier transformed to extract the frequency and spectral widths of vibration. The vibration of aqueous glycerol sessile drops was tracked in real time as the drops evaporated. The changing surface tension and viscosity were extracted using a simple model describing the vibration of a viscous sessile drop. The values of surface tension and viscosity obtained for initial bulk solutions were shown to be in good agreement with literature values, however evaporating drops showed signs of surface contamination after ∼300s. The vibration of sessile drops of aqueous poly(acrylamide-co-acrylic acid) solutions was used to calculate the shear storage and loss moduli using a simple theoretical model. The resulting rheological properties were found to be in agreement with microrheology measurements of the same solutions. The model was also applied to pendant drops of aqueous poly(acrylamide-co-acrylic acid). The majority of the rheological data measured for the pendant drops agreed with microrheology and sessile drop data. Drop vibration therefore provides an accurate method of quantifying the rheological properties of single drops in short time.